34. Growing Virtual Communities - Garber, Debbie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
As online collaborative technologies become easier to use, an increasing range of “virtual communities” are being established, often for educational purposes. This report stresses that an efficient technology is only part of the process underlying a successful online community. It considers the social process on which an online learning community must be founded if it is to flourish and be useful. Definitions of community, learning community, and virtual learning community are reviewed, and the experience of an online community member is discussed. The importance of nurturing the community’s health, and the natural life cycle of a virtual community, are examined.